الجريدة الرسمية العدد 40 مكرر (ب) - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزراء: قرار رقم 3742 لسنة 2025 -- قرار رقم 3743 لسنة 2025 -- قرار رقم 3744 لسنة 2025 -- قرار رقم 3745 لسنة 2025